2021
DOI: 10.1186/s12891-021-04689-5
|View full text |Cite
|
Sign up to set email alerts
|

Different microbial and resistance patterns in primary total knee arthroplasty infections – a report on 283 patients from Lithuania and Sweden

Abstract: Background The microbiology and the susceptibility patterns of infected total knee arthroplasties (TKAs) vary depending on demographic, local antimicrobial stewardship, and surgical factors. We wanted to compare the recent microbial profile and antimicrobial resistance pattern in revisions due to infections after primary TKAs in Sweden and Lithuania. Our hypothesis was that there is a difference in bacteriology and resistance pattern based on patient related, societal and local hospital factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“… 15 Similar to previous reports, we found that the above mentioned microorganisms were mainly seen as part of polymicrobial PJI. 5 , 13 , 16 Polymicrobial PJI was significantly associated with antimicrobial mismatch of the empirical treatment in our cohort. For unknown reasons, polymicrobial PJI was significantly more often seen in RUMC, despite correcting for the difference in patients and surgical characteristics between the hospitals.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“… 15 Similar to previous reports, we found that the above mentioned microorganisms were mainly seen as part of polymicrobial PJI. 5 , 13 , 16 Polymicrobial PJI was significantly associated with antimicrobial mismatch of the empirical treatment in our cohort. For unknown reasons, polymicrobial PJI was significantly more often seen in RUMC, despite correcting for the difference in patients and surgical characteristics between the hospitals.…”
Section: Discussionmentioning
confidence: 67%
“…Enterococci (16%), corynebacteria (18%) and GNB (31%) were more often seen as causatives of PJI in our cohort than is observed in PJI after primary arthroplasty. 4 , 13 , 14 Although some researchers question the relevance of Corynebacterium spp. as causative microorganisms in PJI, Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overwhelming majority of infections after most procedures were caused by Gram-positive cocci, consistent with previous studies. [28][29][30] When looking across the study years, decreasing trends for S aureus specifically were observed for hip fracture repair, shoulder arthroplasty, and spine surgery; a lower rate over time was also observed for ACLR and elective THA, but these were not statistically significant. A recent meta-analysis found S aureus screening and decolonization procedures to be associated with a lower risk of infection after orthopaedic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, identification of the causative pathogen might not be possible in all cases, especially for those patients with culture-negative PJI knowledge of epidemiological data, and antibiotic susceptibilities of the causative pathogens might be helpful to prevent recurrence of PJI. Here, Sebastian et al described in this context differences in the microbiological profiles of patients with PJI between Sweden and Lithuania, with a higher rate of methicillin-resistant S. aureus in Lithuania than in Sweden, outlining the need for further data for better comparison [ 11 ].…”
Section: Introductionmentioning
confidence: 99%